Improving The Quality of Students' Paragraph Writing Through Peer Assessment - Cecep Agus; Yeti Nurhayati (Asian Journal of Social and Humanities, 2022)
The method used in this research is classroom action research design. The primary objectives of this research are to describe the teaching and learning process on paragraph writing through peer-assessment, to establish the amount of influence over the improvement of students ability in paragraph writing. The instruments employed to gain the data are through paragraph writing tests and observation. The tests are given before and after giving the treatment of peer assessment to appraise their own performance; furthermore, the observation is conducted to observe the teaching and learning writing process in the classroom using continuous assessment. The subjects of the research are the students of English Department who are at the fourth semester and join the subject of Writing III at Cirebon STIBA INVADA. The results of the students’ paragraph writing are then analyzed on the basis of the paragraph elements and the scoring procedure according to analytic scale for rating composition proposed by Brown and Bailey. The data are analyzed qualitatively through identification and classification; additionally, they are interpreted using comparative analysis. The results of the research is that the students ability increase substantially after participating in peer assessment. The average score for all paragraph elements is improving; the average score in pretest is 36.41, meanwhile the employing of peer assessment has given rise to the score in post test by 64.35; on the whole, the students’ ability on paragraph writing increases by 43.42%. Thus the evidence seems to be strong that peer assessment can do significantly for students’ achievement in writing.